Management of lean waste in a public higher education institution. (1st March 2021) - Klein, Leander Luiz; Tonetto, Mirela Schramm; Avila, Lucas Veiga; Moreira, Rodrigo
Abstract: The Lean approach and practices are spread around the world and are gaining space in different areas such as public services and Higher Education. The Lean focus on eliminating waste may be applied in every organization, but it is essential to know the wastes and treat them to create value to final process users. Based on this, the objective of the paper is to propose a lean management framework applied to waste management in public higher education institutions (HEI) and to test it into the field. The Analytical Hierarchy Process (AHP) methodology was utilized and applied in a Brazilian Higher Education Institution (HEI). The seven classical Lean manufacturing wastes plus the knowledge waste were taken to make a multi-criteria matrix composed of 24 wastes. The wastes were scored and categorized according to the answers of the directors and vice directors of the HEI studied. As the main result, this study proposes a waste management framework with examples to orientate managers as well as academic and service university staff about wastes. Also, the results demonstrate that loss of knowledge and over-processing wastes are the most relevant to be treated at the university campuses. The waste prioritization allows universities to organize their activities and select tools or practices to optimize their efforts to create value for final users. This study advances in the theoretical and practical field by showing a simple way to incorporate lean practices and values in public service organizations and HEI. Highlights: Lean philosophy has a wide little explored field of application in public services and HEIs. Lean approach allows HEIs to optimize their processes and add value to them. Treating types of waste is essential in public services and in HEIs. HEIs are the gateway to the dissemination of best practices.